Integrated Intelligent Computing, Communication and Security - Krishna, A.N.; Srikantaiah, K.C.; Naveena, C.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights the emerging field of intelligent computing and developing smart systems. It includes chapters discussing the outcome of challenging research related to distributed computing, smart machines and their security related research, and also covers next-generation communication techniques and the networking technologies that have the potential to build the future communication infrastructure. Bringing together computing, communications and other aspects of intelligent and smart computing, it contributes to developing a roadmap for future research on intelligent systems.
Intelligent Systems -- Machine Vision -- Communications -- Security -- e-Learning, e-Business.
Keywords: Computational intelligence; Electronic commerce; Telecommunication; Image processing -- Digital techniques; Computer vision; Computational Intelligence; e-Commerce and e-Business.; Communications Engineering, Networks; Computer Imaging, Vision, Pattern Recognition and Graphics